2009
DOI: 10.1073/pnas.0900028106
|View full text |Cite|
|
Sign up to set email alerts
|

Progressive lengthening of 3′ untranslated regions of mRNAs by alternative polyadenylation during mouse embryonic development

Abstract: The authors wish to note the following: ''We wish to add direct references to a stochastic model of DNA replication previously applied to the Xenopus laevis early embryonic divisions. That model was applied to molecular combing experiments on cellfree extracts from Xenopus laevis embryos.'' The additional references appear below. www.pnas.org/cgi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
548
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 546 publications
(588 citation statements)
references
References 35 publications
38
548
2
Order By: Relevance
“…Other tumor suppressors, such as CSR1 and Cdc73, have also been shown to functionally associate with 3 0 processing factors, such as CPSF3 (Zhu et al, 2009) and CPSF/ CstF (Rozenblatt-Rosen et al, 2009). Recently, it has been shown that the use of alternative mRNA 3 0 cleavage and polyadenylation sites can control the expression of certain genes by eliminating or including several cis-acting elements, such as microRNA target sites and AU-rich elements, in cancer cells and during development (Sandberg et al, 2008;Zlotorynski and Agami, 2008;Ji et al, 2009;Mayr and Bartel, 2009;Singh et al, 2009). Although more work is necessary to determine the functional relevance of the CstF/BARD1/ p53 interaction in the regulation of expression of specific genes involved in DDR, it is possible that the p53-mediated inhibition of mRNA 3 0 processing might also play a role in the selection of different alternative mRNA 3 0 cleavage sites and, consequently, in the regulation of the mRNA levels of genes involved in DDR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other tumor suppressors, such as CSR1 and Cdc73, have also been shown to functionally associate with 3 0 processing factors, such as CPSF3 (Zhu et al, 2009) and CPSF/ CstF (Rozenblatt-Rosen et al, 2009). Recently, it has been shown that the use of alternative mRNA 3 0 cleavage and polyadenylation sites can control the expression of certain genes by eliminating or including several cis-acting elements, such as microRNA target sites and AU-rich elements, in cancer cells and during development (Sandberg et al, 2008;Zlotorynski and Agami, 2008;Ji et al, 2009;Mayr and Bartel, 2009;Singh et al, 2009). Although more work is necessary to determine the functional relevance of the CstF/BARD1/ p53 interaction in the regulation of expression of specific genes involved in DDR, it is possible that the p53-mediated inhibition of mRNA 3 0 processing might also play a role in the selection of different alternative mRNA 3 0 cleavage sites and, consequently, in the regulation of the mRNA levels of genes involved in DDR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the regulation of mRNA 3 0 end formation can have significant roles in cancer (Kleiman and Manley, 2001;Topalian et al, 2001;Scorilas, 2002;Rozenblatt-Rosen et al, 2009). Most importantly, alternative mRNA cleavage and polyadenylation changes the length of the 3 0 -untranslated region and regulates gene expression of different mRNAs in cancer cells (Mayr and Bartel 2009;Singh et al, 2009) and during cell differentiation (Sandberg et al, 2008;Zlotorynski and Agami, 2008;Ji et al, 2009). Cleavagestimulation factor (CstF) is one of the essential 3 0 processing factors and is most likely active as a dimer of an heterotrimer, consisting of three protein factors called CstF3, CstF2 and CstF1.…”
Section: Introductionmentioning
confidence: 99%
“…Several independent studies have revealed the remarkable fact that either levels of cell proliferation or developmental stage can cause a shift in APA from more distal to more proximal PAS selection Ji et al 2009;Mayr and Bartel 2009). In particular, rapidly dividing cells, as are often found in cancerous tissues, tend to use proximal PAS, while cells in later developmental stages tend to use more distal PAS.…”
Section: Alternative Pas (Apa) Define Different Mrna 39 Utrsmentioning
confidence: 99%
“…In general, cleavage/ poly(A) factors appear to be constitutively expressed, and little evidence exists for the selective use of factors for one PAS versus another. However, it has been observed that some cleavage/poly(A) factors may be present at lower, limiting levels in some cells, such as CstF-64 in pre-B cells (Takagaki and Manley 1998;Ji et al 2009). In this situation, stronger PAS will have a significant kinetic advantage (see below).…”
Section: Alternative Pas (Apa) Define Different Mrna 39 Utrsmentioning
confidence: 99%
“…Large numbers of alternatively spliced exons are coordinately regulated during various processes, including notably cell differentiation and cancer 1,2 , but studies mainy focused on cassette exons. Likewise, alternative polyA sites are widely regulated during several processes, most notably cell proliferation, where shorter forms are preferentially expressed [3][4][5][6][7] , but studies mainly focused on tandem polyA sites, which are located in the same exon. Thus, little is known about the regulation of alternative 3 0 terminal exons, also called alternative last exons (ALEs), which are found in 43,000 human genes and correspond to the alternative use of intronic polyA sites in a splicing-dependent manner [7][8][9] .…”
mentioning
confidence: 99%